The Influence of Participative Leadership Style on Job Satisfaction with Organizational Citizenship Behavior as a Moderating Variable - Anshar Daud; Sumardi; Arifhan Ady Dj; Happy Adianita; Yohanes Jibrail Mado (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Researchers believe that a leadership style that involves subordinates/employees in deciding things, is interactive with subordinates, has good closeness, and gives trust to employees can increase employee job satisfaction. Therefore, this research aims to analyze the influence of Participative Leadership Style on employee job satisfaction. Different from previous research, this research adds the Organizational Citizenship Behavior variable as a moderating variable which researchers believe can strengthen the influence of the Participative Leadership Style variable on Job Satisfaction. This research is quantitative research with an explanatory approach. The data used in this research is classified as primary data because the data collection method uses a questionnaire method which is distributed online to 300 Bank Permata employees spread throughout Indonesia. These data are used using the smart PLS 4.0 analysis tool. The result in this article show that Participative Leadership Style variable has a positive relationship and a significant influence on Job Satisfaction because the P-Values results are positive and are below the 0.05 significance level, namely 0.006. Apart from that, the Organizational Citizenship Behavior variable can moderate the influence of the Participative Leadership Style variable on job satisfaction because the positive p-values are below 0.05, namely 0.000. Even smaller than direct testing, 0.006. Thus, the first and second hypotheses in this research can be accepted and proven.